Emotions unveiled - Knaus, Kordula (Muzikološki zbornik, 2012)
The article examines romantic comedies and romances whose narrative includes a scene where the protagonists attend an opera performance. An analysis of opera scenes in Moonstruck (1987), Pretty Woman (1990), and Little Women (1994) will answer questions about the purpose and function of opera in the genre of romance and base these findings in a broader discussion on the importance of the soundtrack for romantic comedy/romance and the particular genre conventions.
Keywords: filmi; ljubezenski filmi; opere; romance; romantic comedy; romantične komedije; soundtrack; zvočni filmski trak